The Combined Effects of Technology Integration and Cultural Sensitivity on Early Learners’ Development: Analysis in Lahore and Nankana Sahib - Dr. Abdul Qayyum; Dr. Mahvish Fatima Kashif; Dr. Faiza Shaheen; Dr. Abrar Hussain Qureshi (Research Journal of Psychology, 2025)
Aims: This study aimed to investigate how the integration of technology, when aligned with cultural sensitivity, influences the cognitive, social-emotional, and academic development of early learners in Pakistan. Background: As Early Childhood Education (ECE) evolves, there is growing emphasis on leveraging technology to enhance learning. However, the success of such initiatives often depends on their cultural relevance. In Pakistan, where diverse cultural norms shape educational experiences, the fusion of digital tools with cultural sensitivity holds untapped potential. Methods: A mixed-methods approach was employed, combining quantitative surveys with qualitative classroom observations and teacher-parent interviews. The study was conducted across public and private ECE settings in Lahore and Nankana Sahib Districts. Results: Findings indicated that children exposed to culturally relevant, well-integrated technology showed marked improvement in engagement, language acquisition, social interaction, and academic readiness. Implications: The study recommends national policy reforms, targeted teacher training, and the development of culturally responsive digital resources to ensure equitable, effective technology use in ECE across Pakistan.